Maternal prothrombin time as an independent predictor of neonatal sepsis: A retrospective case–control study - Gökçenur Karakelleoğlu; Elif Ceren Nur Kırımlı Yanık; Şenol Bozdağ (PLoS ONE, 2026)
Objective To evaluate the diagnostic performance of maternal hemostatic and inflammatory markers in predicting neonatal sepsis. Methods This retrospective case–control study included 176 newborns, of whom 37 were diagnosed with neonatal sepsis and 139 were healthy controls. Maternal blood samples collected at delivery were analyzed for white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet count (PLT), prothrombin time (PT), activated partial thromboplastin time (aPTT), international normalized ratio (INR), and systemic inflammatory indices (SII, SIRI, PIV). Group comparisons were performed using the Mann-Whitney U and Chi-square tests. Predictive markers were assessed using multivariate logistic regression and ROC curve analysis. Results Maternal PT was significantly higher in the sepsis group (p < 0.001), and multivariate logistic regression identified PT as the only independent predictor of neonatal sepsis (OR: 1.79; 95% CI: 1.39–2.31; p < 0.001). ROC analysis showed PT had the highest diagnostic accuracy (AUC: 0.909). The optimal cut-off value for PT was 10.25 seconds, yielding a sensitivity of 89.2% and specificity of 68.3%. Conclusion Maternal PT demonstrates excellent diagnostic accuracy in predicting neonatal sepsis. As one of the first studies to apply logistic regression and ROC analysis solely to maternal hemostatic and inflammatory markers, our findings suggest that maternal PT could serve as a valuable, easily obtainable biomarker for early neonatal sepsis risk stratification.